(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2021)
In the first part of this article, the nature of so-called culturemes is studied, understood as semiotic units referring to an element belonging to a given culture which is unknown or without an exact equivalent in other cultures, and which is therefore perceived as a cultural specificity. Additionally, criteria are examined for both their traditional classification by referential content, and their classification by semiotic relevance in a translation. In the second part, the cultural-traductological method is used to analyse culturemes present in Rudin, the work by Iván Turguéniev, and the way of transposing these in the different Spanish versions by different translators.